Novel glycosyl pyridyl-triazole@palladium nanoparticles: efficient and recoverable catalysts for C–C cross-coupling reactions. Issue 4 (16th February 2015) - Shen, Hongyun; Shen, Chao; Chen, Chao; Wang, Anming; Zhang, Pengfei
Abstract : A series of glycosyl pyridyl-triazole@palladium nanoparticles have been prepared and applied in efficient C–C coupling such as Suzuki–Miyaura coupling, Heck reaction and Sonogashira reaction. Abstract : We report the development of a series of glycosyl pyridyl-triazole@palladium nanoparticles (GPT–Pd) which were synthesized by the reaction of azidoglycosides with 2-ethynylpyridine via click chemistry. These palladium nanoparticles were obtained in high yields and were fully characterized by 1 H and 13 C NMR, elemental analysis, transmission electron microscopy, and thermogravimetric analysis. The single crystal structure of GPT–Pd catalyst5c was determined to show that the glycosyl pyridyl-triazole coordinated with palladium in a bidentate ( N, N ) coordination mode. Their use in palladium-catalyzed C–C coupling reactions such as Suzuki–Miyaura coupling, Heck reaction and Sonogashira reaction achieved quantitative production under mild conditions. Furthermore, the catalysts can be easily separated from the reaction mixture and the catalytic activity remained unchanged even after 8 successive catalytic cycles.